A longitudinal mixed methods evaluation of a facilitation training intervention to build implementation capacity - Costea, Veronica-Aurelia; Bäck, Annika; Bergström, Anna; Lundin, Andreas; Hasson, Henna; Eriksson, Leif (Frontiers in Health Services, 2024)
BackgroundThere is a demand for facilitators who can ease the collaboration within a team or an organization in the implementation of evidence-based interventions (EBIs) and who are positioned to build the implementation capacity in an organization. This study aimed to evaluate the results the Building implementation capacity for facilitation (BIC-F) intervention had on the participants' perceived knowledge, skills, and self-efficacy to facilitate implementation and the normalization of a systematic implementation model into their work routines, and its use into their respective organizations.MethodsThe BIC-F intervention was delivered to 37 facilitators in six workshops, which focused on teaching participants to apply a systematic implementation model and various facilitation tools and strategies. A longitudinal mixed methods design was used to evaluate the intervention. Data was collected pre- and post-intervention using questionnaires and semi-structured interviews grounded on the Normalization Process Theory (NPT). Quantitative data were analyzed using descriptive (mean, SD) and inferential (paired t-tests) methods. Qualitative data were analyzed using deductive content analysis according to NPT.ResultsAn increase in the participants' perceived knowledge, skills, and self-efficacy was observed post-intervention. Normalization of the systematic implementation model in the participants' work routines was in an early phase, facilitated by high coherence, however, other NPT mechanisms were not sufficiently activated yet to contribute to full normalization. In the organizations where participants initiated the normalization process, they were still working towards achieving coherence and cognitive participation among relevant stakeholders.ConclusionThe intervention had positive results on the participants' perceived knowledge, skills, and self-efficacy and these recognized the value of a systematic implementation model for their practice. However, further efforts are needed to apply it consistently as a part of their work routines and in the organization. Future interventions should provide long-term support for facilitators, and include methods to transfer training between organizational levels and to overcome contextual barriers.